It can be unnecessary to combine common synovial fluid analysis and alpha-defensin tests for periprosthetic joint infection diagnosis - Hao Li; Rui Li; Niu Erlong; Wei Chai; LiBo Hao; Chi Xu; Jun Fu; Jiying Chen; Fangzheng Zhu (BMC Musculoskeletal Disorders, 2023)
Abstract Background Periprosthetic joint infection is a serious complication after total joint arthroplasty. Despite that alpha-defensin was used as diagnostic test in the 2018 ICM (international consensus meeting) criteria, its position in the PJI diagnostic pipeline was controversial. Therefore, we performed a retrospective pilot study to identify whether synovial fluid alpha-defensin test was necessary when corresponding synovial fluid analysis (WBC count, PMN% and LE tests) was performed. Methods Between May 2015 and October 2018, a total of 90 suspected PJI patients who underwent revisions after TJA were included in this study. Based on the 2018 ICM criteria, the interobserver agreements between preoperative diagnostic results and postoperative diagnostic results and the interobserver reliability between preoperative diagnostic results and postoperative diagnostic results with or without synovial fluid alpha-defensin tests were calculated. After that, the ROC analysis, and the direct cost-effectiveness of adding alpha-defensin was performed. Results There were 48,16 and 26 patients in the PJI group, inconclusive group and non-PJI group, respectively. Adding the alpha-defensin tests into 2018 ICM criteria can’t change the preoperative diagnostic results, postoperative diagnostic results, and the concordance between preoperative and postoperative diagnostic results. Moreover, the Risk–benefit Ratio is over 90 per changed decision and the direct cost-effectiveness of alpha-defensin was more than $8370($93*90) per case. Conclusions Alpha-defensin assay exhibit high sensitivity and specificity for PJI detection as a standalone test based on the 2018 ICM criteria. However, the additional order of Alpha-defensin can’t offer additional evidence for PJI diagnosis when corresponding synovial fluid analysis was performed (synovial fluid WBC count, PMN% and LE strip tests). Evidence level Level II, Diagnostic study.